Rekonstruksi Penegakan Hukum Tindak Pidana Politik Uang dalam Pemilihan Umum - Erni Dwita Silambi; Emiliana B Rahaili; Rosnida Rosnida; Satriadi Satriadi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
The handling of money politics in terms of legal substance has been regulated in the Election Law which was initially handled by the Sentra Gakkumdu consisting of Bawaslu, the Police, and the Attorney General's Office.This study aims to identify and analyze: to reconstruct the law enforcement of Money Politics Crimes in Elections. This research uses the type of empirical juridical research, namely by studying the applicable rules and also looking for data in the field related to money politics. The results of this study indicate that there are many cases of money politics that occur in the general election process, so their handling must also be more serious. Currently, the crime of money politics in election is in the realm of general criminal acts, so it will be more effective if the handling is delegated to the realm of criminal acts of corruption